NILAI KEISLAMAN DAN KEARIFAN LOKAL DALAM PENGEMBANGAN PARIWISATA HALAL PASCA COVID 19 DI KOTA MALANG - Budiyono Santoso; Muhammad Djakfar (DPPM Universitas Pelita Bangsa, 2022)
Cultural and religious values ​​have great potential in the development of halal tourism. Religious values ​​and local wisdom can play a role both in destination development and in tourist services. The city of Malang as one of the pilots of the halal tourism city project, can take advantage of Islamic values ​​and local wisdom that exists in the community to develop halal tourism. This article seeks to explore Islamic values ​​and local wisdom of the people of Malang City and their implementation in the development of halal tourism. This study proposes prophetic traits (shiddiq, amanah, tabligh, fathonah) as Islamic values ​​to be used in the development of halal tourism in Malang City. Meanwhile, diversity, progressiveness and egalitarianism are values ​​of local wisdom that support the development of Halal tourism in Malang City. The prophetic nature in the development of halal tourism in Malang is implemented, one of which is the commitment to meet the standard of the halal assurance system, Clean, Health, Safety, and Environmental Sustainability (CHSE) certification, attention to environmental sustainability, community empowerment and the development of promotional innovations with information technology and social media. While the